Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

The expression is in the form of a³ - b³

(a +b)³ - (2a - 2b)³ = [ a + b - (2a -2b) ] [ (a+b)² + (a+b)2(a-b)+(2a-2b)² ]

= (3 b - a) [ a² + b² + 2 a b + 2 a² - 2b² + 4a² + 4b² -8ab ]

= (3 b - a) (7 a² - 3 b² - 6 a b ) --- step 1

= (3 b - a) 7 [ a - b (3 +√30)/7 ] [ a - b (3 -√30)/7 ]

The factors of the second factor on the RHS in step 1, can be found using quadratic equation equating it 0.

(a +b)³ - (2a - 2b)³ = [ a + b - (2a -2b) ] [ (a+b)² + (a+b)2(a-b)+(2a-2b)² ]

= (3 b - a) [ a² + b² + 2 a b + 2 a² - 2b² + 4a² + 4b² -8ab ]

= (3 b - a) (7 a² - 3 b² - 6 a b ) --- step 1

= (3 b - a) 7 [ a - b (3 +√30)/7 ] [ a - b (3 -√30)/7 ]

The factors of the second factor on the RHS in step 1, can be found using quadratic equation equating it 0.